Dampak Pertambangan Batubara Dalam Kehidupan Sosial Ekonomi Masyarakat di Desa Apung Kecamatan Tanjung Selor Kabupaten Bulungan - N, Jimmy; Merang, K. Rapiandi Isak (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2020)
The problem in the research study is how the impact of coal mining on the socio-economic life of the community in Apung Village, Tanjung Selor District, Bulungan Regency. The research method is descriptive qualitative, with research informants including the Head of the Floating Village, the Secretary of the Floating Village, community leaders, and the community of the Floating Village. Data collection techniques are observation, interviews, and documentation. Data analysis, namely data reduction, data presentation (data display), and drawing conclusions / verification. The validity of the data included source triangulation, method triangulation, and research time extension. The impact of coal mining on the socio-economic life of the people in Apung Village, namely the existence of coal mining has a positive impact on the socio-economic conditions of the Apung Village community, including the availability of jobs for the local community, improving the local community's economy by providing assistance: (1) chicken and catfish farming, (2) giving citrus seeds to the farming community (3) giving cassava seeds, (4) providing clean water (water storage), (5) provide social assistance in the form of basic necessities, (6) building infrastructure in the form of roads and infrastructure in the form of repair of village road bodies, build roads between villages and build sports fields, (7) provide assistance for community service / public work in Apung village. The next positive impact is the increase in local community business, namely the food business continues to increase and shop / or sales, increase water depot business, and open a ketring business. The negative impact of mining companies, namely, deforestation, loss of flora and fauna, reduced land for agricultural activities, pollution of several water flows, dust or air pollution, and land disputes between communities.